Upaya Meningkatkan Kemampuan Desain Pembelajaran Etnosain Guru Biologi untuk Keberlanjutan - Sriyati, Siti; Solihat, Rini; Siswandari, Puti; Puspitaningrum, Hardini; Purwianingsih, Widi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of this activity is to improve biology teachers’ ability to design ethnoscience-based learning to support the concept of sustainability. Research methodology: The training used the lesson study (plan-do-see) activity pattern. The activity was carried out in four meetings (three online and one offline) held from July to September 2024. Learning was implemented at one of the SMA N in Singaparna, Tasikmalaya, West Java. Results: The results of this training activity show that the teaching modules prepared by teachers by integrating local wisdom or potential with biology materials can be carried out by 93.5% (very good). The results of the questionnaire show that 100% of teachers consider the integration of local wisdom/local potential into biology material important, because it can increase students' understanding of concepts (100%) and can increase character values and student sustainability (100%). For teachers, learning based on local wisdom adds insight into innovative learning and becomes more sensitive to recognizing the local wisdom/potential of their region (92.7%). Conclusions: Biology teachers successfully designed ethnoscience-based learning modules to support sustainability, as demonstrated by the production of eight teaching modules and their effective classroom implementation (93.5%). Teachers responded positively, with 92.3% becoming more aware of local wisdom and 100% agreeing that it enhances character and sustainability values. Limitations: Student response data were not taken, even though it was necessary to confirm the results of teachers' responses to ethnoscience-based learning. Contribution: Improve teachers' ability to design ethnoscience-based teaching materials, improve students' understanding of concepts, and shape students' character values and sustainability.